Biocompatible aloe vera and tetracycline hydrochloride loaded hybrid nanofibrous scaffolds for skin tissue engineering - Ezhilarasu, H.; Ramalingam, Raghavendra; Dhand, Chetna; Lakshminarayanan, Rajamani; Sadiq, Asif; Gandhimathi, Chinnasamy; Ramakrishna, Seeram; Bay, Boon Huat; Venugopal, Jayarama Reddy; Srinivasan, Dinesh Kumar (MDPI AG, 2019)
Aloe vera (AV) and tetracycline hydrochloride (TCH) exhibit significant properties such as anti-inflammatory, antioxidant and anti-bacterial activities to facilitate skin tissue engineering. The present study aims to develop poly-"-caprolactone (PCL)/ AV containing curcumin (CUR), and TCH loaded hybrid nanofibrous sca_olds to validate the synergistic e_ect on the fibroblast proliferation and antimicrobial activity against Gram-positive and Gram-negative bacteria for wound healing. PCL/AV, PCL/CUR, PCL/AV/CUR and PCL/AV/TCH hybrid nanofibrous mats were fabricated using an electrospinning technique and were characterized for surface morphology, the successful incorporation of active compounds, hydrophilicity and the mechanical property of nanofibers. SEM revealed that there was a decrease in the fiber diameter (ranging from 360 to 770 nm) upon the addition of AV, CUR and TCH in PCL nanofibers, which were randomly oriented with bead free morphology. FTIR spectra of various electrospun samples confirmed the successful incorporation of AV, CUR and TCH into the PCL nanofibers. The fabricated nanofibrous sca_olds possessed mechanical properties within the range of human skin. The biocompatibility of electrospun nanofibrous sca_olds were evaluated on primary human dermal fibroblasts (hDF) by MTS assay, CMFDA, Sirius red and F-actin stainings. The results showed that the fabricated PCL/AV/CUR and PCL/AV/TCH nanofibrous sca_olds were non-toxic and had the potential for wound healing applications. The disc di_usion assay confirmed that the electrospun nanofibrous sca_olds possessed antibacterial activity and provided an e_ective wound dressing for skin tissue engineering.